Manual Acupuncture for Optic Atrophy: A Systematic Review and Meta-Analysis. (1st January 2019) - Zhi, Fang-Yuan; Liu, Jie; Ma, Xiao-Peng; Hong, Jue; Zhang, Ji; Zhang, Dan; Zhao, Yue; Wu, Li-Jie; Yang, Yan-Ting; Wu, Dan-Yan; Xie, Chen; Wu, Ling-Xiang; et al.
Abstract : Objectives. This systematic review aims to critically evaluate the efficacy of manual acupuncture for optic atrophy. Eight English and Chinese databases, including Cochrane Library, EMbase, PubMed, Chinese National Knowledge Infrastructure (CNKI), Wanfang Database, China Science and Technology Journal Database (VIP), and Chinese Biomedical Literature Database (CBM), as well as ongoing trials registered with the WHO International Clinical Trials Registry Platform, were searched to identify eligible randomized controlled trials (RCTs) studying manual acupuncture for optic atrophy compared to medication alone. The quality of evidence was assessed using Cochrane Collaboration's risk of bias tool. Meta-analysis was performed using Review Manager version 5.3. Nine studies were identified and included for meta-analysis. The meta-analysis showed significant differences in favor of manual acupuncture or manual acupuncture plus medication compared with medication alone in the following outcome measures: visual acuity (MD = 0.18, 95% CI [0.17, 0.20], P < 0.00001), mean sensitivity of visual field (MD = 2.11, 95% CI [1.90, 2.32], P < 0.00001), the latent period of P-VEP100 (MD = -6.80, 95% CI [-8.94, -4.66], P < 0.00001), the total effectiveness (264 eyes) (OR = 3.22, 95% CI [1.88, 5.51], P <0.0001), and the total effectiveness (344 participants) (OR = 4.29, 95% CI [2.56, 7.19], P < 0.00001). Despite statistical advantages of manual acupuncture in the literature, due to serious methodological flaws in study design, it cannot be concluded that manual acupuncture is more effective than medicine alone. It is essential that a properly controlled clinical trial is designed and controls are established to exclude placebo effects.